Dysthyroxinaemia Among Sub-fertile Female Clients Attending Nizamiye Hospital, Abuja, Nigeria. - Biliaminu, S.A.* , AbdulAzeez, I.M. , Khan, N. , Bakr, M.R. , Oladosu, W.O. , Yusuff, J.O. and Okesina, A.B. (Sokoto Journal of Medical Laboratory Science)
Disorders of thyroid function is very common in the population and affects many systems including the reproductive system, hence its causal role in infertility in women cannot be overemphasized. This makes it relevant in the algorithm of reproductive dysfunction. The aim of this study was to determine the pattern and prevalence of dysthyroxinaemia among infertile females visiting Nizamiye Hospital, Abuja, Nigeria. This was a retrospective study of thyroid function test and other parameters of infertile females in a private hospital setup between January 2015 and December 2019. Data were analyzed using Statistical Software for Social Sciences (SPSS Version 21). The 52 infertile females included in this study had mean age of 32.65±5.21 years. The youngest of them was 22 while the oldest was 42 years old. Twenty-two (42.3%) and 30 (57.7%) of them had primary and secondary infertility respectively. Of all the subjects 20 (38.5%) were euthyroid, 21(40.4%) had 2 o hypothyroidism, 9(17.3%) had 1 o hypothyroidism while 2(3.8%) had subclinical hypothyroidism. Other variants of dysthyroxinaemia were not present amongst the subjects. There was a higher prevalence of dysthyroxinaemia in our study than in previous studies. However, 2 o hypothyroidism was found to be the commonest among the subjects in this study which was essentially in contrast with subclinical hypothyroidism found in previous studies. Thyroid function test should be encouraged in infertile female subjects for proper and prompt management to improve both natural fertility, spontaneous conception as well as conception rates with assisted reproductive therapy.